Real-Time PCR Assay for the Diagnosis and Quantification of Co-infections by Diaporthe batatas and Diaporthe destruens in Sweet Potato - Fujiwara, Kazuki; Kobayashi, Yuki O.; Usui, Manami; Nishioka, Kazuya; Nakamura, Misa; Kawano, Shinji; Okada, Yoshihiro; Kobayashi, Akira; Miyasaka, Atsushi; Hirayae, Kazuyuki; Kushima, Yoshiyuki; Nishi, Yatsuka; et al. (Frontiers in Plant Science, 2021)
Foot rot disease caused by Diaporthe destruens (formerly Plenodomus destruens) has become a major concern for the production of sweet potato [Ipomoea batatas (L.) Lam.] in Japan. A related fungus Diaporthe batatas, which causes dry rot disease of sweet potato, is native and is widespread in fields in Japan. The similar characteristics of these two pathogens pose a challenge for conventional disease diagnosis. Currently, there are no effective molecular measures for identifying and distinguishing D. destruens and D. batatas. Here, we demonstrate a real-time PCR assay that distinguishes and quantifies D. batatas and D. destruens from co-infected sweet potato. The assay was performed with various simulated DNA combinations of D. batatas and D. destruens ranging from 1:1 to 1:100000. The assay was also used with the ratios of D. batatas: D. destruens: sweet potato DNA ranging from 1:1:1 to 1:1:100000. These assays produced a specific amplification product for each of the pathogens, and quantified the fungal biomass over the entire range tested without detecting false positives. The assay was validated by using infected sweet potato collected from various fields; it showed sufficient sensitivity and specificity to quantify and distinguish D. batatas and D. destruens from these field samples. Thus, our real-time PCR assay would be a useful tool for diagnosis of D. batatas and D. destruens and is expected to provide the foundation for the design of integrated disease management strategies for foot rot disease in sweet potato.